Chapter Il Laurenziano Pluteo 42, 3 e la tradizione caratterizzante del Decameron - Monaco, Giulia (Studi e saggi, 2021)
The aim of this article is to illustrate the most relevant results of the philological and textual analysis that I accomplished on a witness of Boccaccio's Decameron, MS. Firenze, Bibl. Medicea Laurenziana, Plut. 42, 3. The work consisted in an integral collation, based on two Giornate and some loci critici, between Plut. 42, 3 and the most authoritative tradition of Decameron (MSS. Berlin, Staatsbibl., Ham. 90, Paris, Bibl. nationale de France, It. 482 and Firenze, Bibl. Med. Laur., Plut. 42, 1). On one hand, the purpose of this work is to demonstrate that the text transmitted by Plut. 42, 3 is contaminated and altered by errors and innovations, therefore unusable for a new critical edition of the work; on the other hand, it leads us to an investigation into the existence of a «characterizing tradition» of Decameron.